2017
DOI: 10.1039/c7ee02048a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable hysteresis effect for perovskite solar cells

Abstract: Perovskite solar cells (PSCs) usually suffer an anomalous hysteresis in current-voltage measurements that leads to an inaccurate estimation of the device efficiency. Although ion migration, charge trapping/detrapping and accumulation have been proposed as a basis for the hysteresis, the origin of hysteresis has not been apparently unraveled. Herein we reported a tunable hysteresis effect based uniquely on open-circuit voltage variations in printable mesoscopic PSCs with a simplified triple-layer TiO2/ZrO2/Carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
204
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(211 citation statements)
references
References 42 publications
7
204
0
Order By: Relevance
“…The device with PBDTT exhibited a stable PCE of 19.50% and that with PBTTT displayed a stabilized PCE of 18.46%, which was consistent with their J-V curves ( Figure S4b, Supporting Information). Hysteresis loops are quite dependent on test system, interfacial contact, and perovskite material, [61,62] and the perovskite active layer is very sensitive to the atmosphere of glove box. In particular, the device with PBDTT showed low hysteresis, which should originate from the better interfacial contact between the perovskite and HTL as well as between the HTL and anode.…”
Section: Resultsmentioning
confidence: 99%
“…The device with PBDTT exhibited a stable PCE of 19.50% and that with PBTTT displayed a stabilized PCE of 18.46%, which was consistent with their J-V curves ( Figure S4b, Supporting Information). Hysteresis loops are quite dependent on test system, interfacial contact, and perovskite material, [61,62] and the perovskite active layer is very sensitive to the atmosphere of glove box. In particular, the device with PBDTT showed low hysteresis, which should originate from the better interfacial contact between the perovskite and HTL as well as between the HTL and anode.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] Noticeably, very few studies have been reported regarding their potential to indoor applications for low power consumption wireless electronics such as Internet of Things (IOT) and self-sustainable smart housing. [1,2] Noticeably, very few studies have been reported regarding their potential to indoor applications for low power consumption wireless electronics such as Internet of Things (IOT) and self-sustainable smart housing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In this regard, the selection of materials is of fundamental importance for www.advelectronicmat.de carriers of the silicon substrate and bound surface charges of the BST thin film. [1][2][3][4][5][6][7][8][9][10] In this regard, the selection of materials is of fundamental importance for www.advelectronicmat.de carriers of the silicon substrate and bound surface charges of the BST thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique electronic and optical characteristics, 2D and quasi-2D materials are emerging as exciting material systems for a new generation of layered optoelectronics, [11,12] such as photodetectors, [13,14] polarizers, [15] solar cells, [3,[16][17][18] and optical modulators. Due to their unique electronic and optical characteristics, 2D and quasi-2D materials are emerging as exciting material systems for a new generation of layered optoelectronics, [11,12] such as photodetectors, [13,14] polarizers, [15] solar cells, [3,[16][17][18] and optical modulators.…”
mentioning
confidence: 99%